Pelos caminhos do ódio: da pulsão ao narcisismo - Oliveira Filho, Claudio de (2021)
From the contemporary social panorama and the incidence of hatred in the psychoanalytic clinic, whether manifest or unconscious, the research proposal is a study on hatred in the social, metapsychological and psychopathological dimensions, having Freud and Klein's psychoanalysis as a reference. From the reading of these authors, the ideas were presented following the chronological publication order of texts. The bibliographic review served to investigate the relationship between hatred, narcissism, and the death drive, trying to establish which of these concepts the affection would be closest to. The idea of ‘narcissism of small differences’ and the notion of aggressive drive made it possible to analyze contemporary expressions of hatred in society, based on Freudian contributions. Regarding metapsychology, it is possible to conclude that Freud initially approached hatred to the drive (sadism) and, later, to narcissism also to the death drive. In turn, Klein keeps the hatred in the pulsatory register, close to the death drive, taking little care of narcissism in his theory. This author develops the theory of positions (schizoparanoid and depressive), in which there is participation of hatred. Freudian theory also leaves the concept of narcissism limited, keeping it closer to Eros after 1920. Finally, Green and Rosenfeld articulate between narcissism and death drive, with the concepts of death narcissism and destructive narcissism. In order to illustrate the concepts presented, we chose to analyze the film We need to talk about Kevin, in which the character presents hatred as a form of connection to the object, failing to separate himself from his mother. Such psychic functioning points to a schizoparanoid position, in which there is no integration between love and hate, which resumes the Kleinian theory